Interesting case of uveitis in a child - Gul, Shandana; Gul, Sundas (International Journal of Research in Medical Sciences, 2024)
Childhood uveitis is complex condition, and it is very rear in children compared to adults. It accounts for 5-10% of all uveitis seen in tertiary referral clinics. Prevalence of uveitis is 22 per 100,000 persons. Uveitis in children is commonly asymptomatic. It can become chronic and cause damage to ocular structure. Diagnosis can be delayed due to various reasons, including preverbal age and difficulties in examining young children. Uveitis morbidities in pediatric patients include cataract, glaucoma, and amblyopia. Close follow up is necessary as uveitis can flare up during immune-modulary therapy. Here, we represent an interesting case of uveitis in a 7 years old boy who had idiopathic uveitis and presented with red eye which is most common presentation in primary care.